Users' trust in electronic commerce applications / Ferdinand Jilan Anak Dawie and Mohd Sazili Shahibi - Dawie, Ferdinand Jilan; Shahibi, Mohd Sazili (Universiti Teknologi MARA, 2020)
System security, Ease of Use, Information Clarity, Information Accuracy, Users' Support, and Services Responsiveness were identified as factors that may have a significant relationship with Users' Trust in using EC Applications. There are 330 questionnaires were distributed to young internet users, but 300 data were accepted meanwhile the remaining 30 data were rejected due to incompleteness of the data. The data of this study were analyzed using SPSS and Smart PLS software. The result of this study shows that System Security, Information Accuracy and Responsiveness has significant joint effect with Users' Trust while Ease of Use, Information Clarity and User Support did not show any significant relationship